(untitled) (Research, Society and Development, 2021)
The present work aims to study the influence of the addition of eggshell residues on the compressive strength of conventional concrete. Several surveys have been developed with the purpose of reducing construction costs and investigating appropriate materials, especially those that are not conventional. Agroindustrial activities generate a large amount of waste with potential for a partial replacement of sand and coarse aggregates in the manufacture of mortar and concrete. A product generated in large quantities in hatcheries is eggshell, which, in addition to being a large amount of waste, disposal is a problem, it creates allergies when kept in the trash, also an undesirable smell causing irritation. The concretes were tested for compressive strength at the ages of 14 and 28 days. In relation to the concrete with treated eggshell residues, the reference concrete mix was elaborated by the ABCP-ACI method; the respective percentages of replacement of the volume of fine aggregate by eggshell residues (0% to 30%). The results show that the compressive strength decreased with the increase in the percentage of eggshell residue, which indicated that the composite was suitable for blocks and floors.